2006
DOI: 10.1093/eurheartj/ehl101
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of electrocardiographic abnormalities in hypertrophic cardiomyopathy with cardiac magnetic resonance

Abstract: Abnormal Q waves reflect the interrelation between upper anterior septal thickness and other regions of the left and right ventricles, and wider Q waves are associated with late-enhancement. Conduction disturbances and absent septal Q waves are associated with late-enhancement. The depth of negative T waves is related to craniocaudal asymmetry and apical late-enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 37 publications
4
50
2
1
Order By: Relevance
“…The percentage of hyperenhanced myocardial mass was also larger in these patients. The results of this investigation indicate a close relationship between the extent of myocardial hyperenhancement and ventricular arrhythmias in HCM (9,(12)(13)(14)24). Although the relationship between myocardial hyperenhancement and ventricular arrhythmias or clinical symptoms may be complex, patients with symptomatic apical HCM and widely distributed hyperenhanced myocardium should be followed up rigorously to avoid missing an opportunity for preventive ICD implantation.…”
Section: Relationship Between Ventricular Arrhythmias and The Extent mentioning
confidence: 82%
“…The percentage of hyperenhanced myocardial mass was also larger in these patients. The results of this investigation indicate a close relationship between the extent of myocardial hyperenhancement and ventricular arrhythmias in HCM (9,(12)(13)(14)24). Although the relationship between myocardial hyperenhancement and ventricular arrhythmias or clinical symptoms may be complex, patients with symptomatic apical HCM and widely distributed hyperenhanced myocardium should be followed up rigorously to avoid missing an opportunity for preventive ICD implantation.…”
Section: Relationship Between Ventricular Arrhythmias and The Extent mentioning
confidence: 82%
“…As many as half of patients with ACM are mildly symptomatic or asymptomatic, and many patients have been diagnosed only when giant negative T waves in the left precordial leads are noted incidentally on ECG. 8,23 However, it is also reported that this giant negative T waves may evolve in both positive and negative directions over time. 9,28 Transition from normal T waves to negative T waves can occur acutely or this process can take several years and usually remains unchanged thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Although echocardiographic image enhancement with an intravenous contrast agent 24 and CMR 23 have been shown to improve the visualization of the endocardial-blood interface, clinical attention must be drawn to the unique electrocardiographic features that provide the initial clues to making the diagnosis. In present study, we found that STE in V4-6 derivations in addition to classically giant T wave inversion were well correlated with the presence of apical aneurysm in HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial regions with increased gadolinium concentrations are considered to correspond to the absence of viable myocytes, including post-ischemic necrosis, edema, or areas with augmented extracellular space, such as fibrotic tissue [10][11][12][13]. Late-enhancement is a common feature in patients with HCM and its extension has been described as being related to the severity of hypertrophy, electrocardiographic alterations [14], functional parameters, progression of the disease and risk of sudden death [15][16][17][18]. Until now LE in HCM has been related, as in chronic myocardial infarction, to myocardial fibrosis and increased collagen content [19,20].…”
Section: Introductionmentioning
confidence: 99%